Dengue Vaccine Booster in Healthy Adolescents and Adults in Latin America: Evaluation 4–5 Years After a Primary 3-Dose Schedule. Issue 5 (May 2019) - Coronel, Diana; García-Rivera, Enid J.; Rivera, Maribel; Arredondo-García, José Luis; Dietze, Reynaldo; Perroud, Ana Paula; Cortés, Margarita; Bonaparte, Matthew; Zhao, Jessie; Tila, Mihaela; Jackson, Nick; Zambrano, Betzana; et al.
Abstract : Background: The tetravalent dengue vaccine (CYD-TDV, Dengvaxia, Sanofi Pasteur) demonstrated efficacy in 2 previous phase III trials conducted in endemic countries. Neutralizing antibodies (NAbs) elicited by 3 doses of this vaccine have been associated with efficacy. Long-term follow-up data has shown that NAb immune responses tend to wane over time, after the third dose. This study compared the immune response elicited by a booster (4th) dose of CYD-TDV with the immune responses from the same participants obtained post-dose 3 of the primary series administered 4–5 years earlier. Methods: This multicenter, observer-blind, randomized, placebo-controlled, phase II noninferiority trial was conducted in healthy adolescents and adults in dengue endemic countries of Latin America (Colombia, Honduras, Brazil, Mexico and Puerto Rico). All participants had been immunized with 3 doses of CYD-TDV in phase II studies conducted 4–5 years earlier. NAb levels against each dengue virus serotype 28 days postbooster or placebo injection were reported. Results: A total of 187 participants received CYD-TDV and 64 received placebo. Prospectively defined noninferiority criteria for dengue NAbs after the booster dose compared with postdose 3 were met for all 4 serotypes. Prospectively defined superiority criteria were met for 3 of the 4 serotypes. Conclusions: Antidengue NAb levels can be boosted to levels at least as high as, or higher than those observed after completion of the primary 3-dose series, with an additional dose of CYD-TDV 4–5 years after the standard 3-dose vaccination schedule.